The 'Impossible' Default: Qualitative Data on Borrower Responses to Two Types of Social-Collateral Microfinance Structures in Rural China. Issue 1 (2nd January 2016) - Hsu, Becky
Abstract: Qualitative data reveal how the social context underlying the ties linking borrowers in microfinance programmes influences their decisions. Focusing directly on social context makes it possible to distinguish between two social-collateral structures and explain why one facilitated repayment while the other did not. Fieldwork in rural China shows that the basis of the social ties in the social-collateral structure is central to explaining whether and why individuals decided to sanction defaulters and repay loans. The article closes with reflections on generalisations of these findings to future microfinance research.